2006
DOI: 10.1007/s10620-006-9212-3
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Electrical Stimulation With Parameters for Gastroparesis Enhances Gastric Accommodation and Alleviates Distention-Induced Symptoms in Dogs

Abstract: Gastric electrical stimulation (GES) improves symptoms in patients with gastroparesis. We sought to determine if stimulation at fundus with parameters used for gastroparesis could affect gastric accommodation and distention-induced symptoms in dogs. Nine dogs were implanted with a gastric cannula at the anterior stomach and 1 pair of stimulation electrodes in the fundus. Assessment of gastric accommodation and a series of gastric distention were performed using a barostat. Stimulation parameters were of short … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…To the best of our knowledge, no previous studies have reported the application of GES in the treatment of emetic responses induced by cisplatin. However, previous studies in our laboratory have shown that GES with short pulses improved the symptoms of nausea and vomiting in patients with gastroparesis, or vasopressininduced emetic responses in dogs, with no or minimal effect on gastric motility [17,20,21]. The data obtained in our study are in agreement with the previous findings.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…To the best of our knowledge, no previous studies have reported the application of GES in the treatment of emetic responses induced by cisplatin. However, previous studies in our laboratory have shown that GES with short pulses improved the symptoms of nausea and vomiting in patients with gastroparesis, or vasopressininduced emetic responses in dogs, with no or minimal effect on gastric motility [17,20,21]. The data obtained in our study are in agreement with the previous findings.…”
Section: Discussionsupporting
confidence: 93%
“…These include long-pulse stimulation (pulse width in milliseconds), shortpulse stimulation (pulse width in microseconds) and stimulation with trains of pulses instead of repetitive single pulses. It seems that gastric electrical stimulation (GES) with long pulses is capable of normalizing gastric dysrhythmia and pacing gastric slow waves [12][13][14][15][16], whereas stimulation with short pulses is able to reduce nausea and vomiting [17][18][19][20][21].Several studies have shown that GES using an implantable device, called the Enterra Ò Therapy, produces a significant and sustained improvement in symptoms of vomiting and nausea and in nutritional status in most patients with intractable symptomatic gastroparesis or drug-refractory diabetes [18,19,[22][23][24].However, it is unknown whether this special method of GES is effective in reducing chemotherapy-induced emetic symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…A recent canine study using GES of short pulses or the so-called Enterra Therapy (Medtronic, Minneapolis, MN, USA) (repetitive trains of two short pulses with a pulse frequency of 14 Hz and width of about 300 ls, it could be considered as trains of short pulses) showed a slight but significant reduction of fundic tone and enhancement of postprandial fundic relaxation accompanied by an improvement in gastric distention-induced symptoms in dogs. 45 However, more studies are needed to confirm these findings. Gastric electrical stimulation with long pulses is capable of altering gastric (both fundic and antral) tone substantially in dogs.…”
Section: Gastric Tone and Gastric Accommodationmentioning
confidence: 97%
“…The Enterra Therapy does not alter gastric slow waves 27,36 but may reduce gastric tone and thus improve gastric accommodation as reported in a canine study. 45 Not much information is available regarding the effect of the Enterra Therapy on visceral hypersensitivity. However, two recent preliminary studies in humans seem to suggest a potential role of the therapy in altering visceral hypersensitivity.…”
Section: Ges With Short Pulsesmentioning
confidence: 99%
“…This is frequently impairment in gastoparetic patients and has been shown to improve following GES therapy. 15,[34][35][36][37] However, this phenomenon is likely only an explanation for symptomatic reduction and probably does not describe the improvement in baseline gastric frequency.…”
Section: Discussionmentioning
confidence: 99%